INDUKSI EMBRIO SOMATIK SEKUNDER KOPI ARABIKA DAN DETEKSI KERAGAMAN SOMAKLONAL MENGGUNAKAN MARKA SSRs / Induction of Secondary Somatic Embryos of Arabica Coffee and Detection Somaclonal Variation Using SSRs Marker - Meynarti Sari Dewi Ibrahim; Rr. Sri Hartati; Reflinur Reflinur; Sudarsono Sudarsono (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
The secondary somatic embryogenesis of coffee plant can be used to propagate superior varieties, plant resulted from genetic transformation and mutation. Present study aimed to obtain the best media composition for induction of secondary somatic embryos in solid or semi-solid media, and to evaluate the possibility of somaclonal variations occurrence in the resulting plantlets. Primary somatic embryos torpedo phase of the AS2K variety were used as explant sources. Types of cytokines i.e. 2-iP (4.54 and 9.08 μM), kinetin (9.30 μM) and BAP (BAP 17.76 and 1.33 μM) and medium density (solids and semi-solid) were used as treatments. A total of 20 SSRs marker were used in molecular analysis of plantlets with 10 replication per treatment. The results showed that the media with the addition of BAP 17.76 μM resulted in the highest percentage (75.50%), the highest number of secondary somatic embryos (10.63), the tertiary, quarter and quiner somatic embryos. Number of secondary somatic embryos produced in a dense media was higher than those in the semi-solid media.. Based on molecular analysis, planlets on all treatment were relatively homogenous except on medium with 17.76 μM BAP which indicated by one allelle changing at ssrR209 locus. These findings indicated that the use of culture medium with supplemented with 9.08 μM 2-iP is advisable to induce the secondary somatic embryos due to its capacity to produce high number of somatic embryos and exhibited no somaclonal variations occurred among the plantlets.Keywords: Coffea arabica, tertiary somatic embryos, quarter somatic embryos, quiner somatic embryos, semi solid media AbstrakEmbriogenesis somatik sekunder pada tanaman kopi dapat digunakan untuk memperbanyak varietas unggul, hasil transformasi dan mutasi. Penelitian ini bertujuan untuk mendapatkan komposisi media terbaik dalam menginduksi embrio somatik sekunder dalam media padat maupun semi padat, dan mengevaluasi kemungkinan terjadinya variasi somaklonal pada planlet yang dihasilkan. Eksplan yang digunakan adalah embrio somatik primer fase torpedo dari varietas AS2K. Perlakuan yang diuji adalah jenis sitokinin yaitu: 2-iP (4,54 dan 9,08 μM), kinetin (9,30 μM) dan BAP (BAP 17,76 μM dan 1,33 μM) dan kepadatan media (padat dan semi padat). Analisis molekuler menggunakan 20 primer marka SSRs dengan jumlah ulangan 10 planlet per perlakuan. Hasil penelitian memperlihatkan media dengan penambahan BAP 17,76 μM menghasilkan persentase embrio somatik sekunder tertinggi (75,50%), embrio somatik sekunder terbanyak (10,63), embrio somatik tersier, kuarter dan kuiner. Jumlah embrio somatik sekunder yang dihasilkan pada media padat lebih banyak dibandingkan semi padat. Berdasarkan analisis molekuler, planlet yang dikulturkan pada semua perlakuan relatif seragam, kecuali pada perlakuan BAP 17,76 μM yang menunjukkan telah terjadi perubahan satu alel pada lokus ssrR209. Temuan ini memperlihatkan bahwa penggunaan media kultur dengan 2-iP 9,08 μM lebih dianjurkan untuk menginduksi embrio somatik sekunder karena dapat menghasilkan jumlah embrio somatik cukup banyak dan tidak memperlihatkan adanya variasi somaklonal pada planlet yang dihasilkan.Kata kunci: Coffea arabica, embrio somatik tersier, embrio somatik kuarter, embrio somatik kuiner, media semi-padat